Investigation on Crystallization and Optical Properties of Ca1−xLaxF2+x Glass‐Ceramics. Issue 3 (4th February 2014) - Imanieh, Mohammad H.; Martín, Inocencio R.; Yekta, Bijan Eftekhari; Gonzalez‐Platas, Javier; Creus, Alberto Hernández; Pinckney, L.
<x xml:space="preserve">Abstract</x> Transparent oxyfluoride glass‐ceramics containing Er3+, Yb3+:Ca1−xLaxF2+x nanocrystals, which may have potential applications in the fields of solid‐state laser and luminescence, were prepared. Crystallization of Ca1−xLaxF2+x and behavior of Yb3+ and Er3+ during the heat treatment was investigated. Results showed that alumina content had a significant effect on crystallization of Ca1−xLaxF2+x in the SiO2–Al2O3–CaF2–LaF3 system. Due to the size of phase‐separated areas, the size of the crystals during the heat treatment did not change significantly. After crystallization of Ca1−xLaxF2+x in the glass, the majority of Er3+ ions incorporated into the Ca1−xLaxF2+x crystals during the heat‐treatment process. Time‐resolved luminescence of Er3+ ions in the samples around 842 nm showed that the solubility of Er3+ ions in Ca1−xLaxF3 crystals is higher than pure CaF2 crystals. The glass undergoes an enormous phase separation, which keeps the Yb3+ ions within the other separated phase. Therefore, only at high temperatures (790°C) or with a long heat‐treatment time (72 h), there is a possibility for Yb3+ ions to be incorporated into the fluorine phase.